COMPARATIVE ANALYSIS OF INTENSIFIERS IN ENGLISH, UZBEK, RUSSIAN, TURKISH, GERMAN AND KOREAN (SCIENCE TIME JOURNAL, 2026)
This study compares intensifiers in English, Uzbek, Russian, Turkish, German, and Korean, analyzing their structural, semantic, and functional features. It highlights typological differences and similarities in expressing degree, emphasis, and speaker attitude across languages.